Enhancing Supply Chain Resilience: A Narrative Review of Risk Mitigation Strategies - Judijanto, Loso; Wufron, Wufron (Yayasan Sinergi Kawula Muda, 2024)
This narrative review examines current strategies and challenges in supply chain risk mitigation, emphasizing technological, institutional, and collaborative aspects. In response to global disruptions, technologies like AI, Big Data, and IoT enhance supply chain resilience through real-time visibility, predictive forecasting, and adaptive responses. Despite their potential, implementation remains uneven due to structural and contextual barriers. A structured literature review and thematic analysis reveal that while advanced technologies improve decision-making, issues such as operational rigidity, information asymmetry, regulatory hurdles, and supplier dependence persist. Collaborative models, supported by digital platforms and institutional policies, enhance adaptability and performance. Policy tools like supply chain finance and multi-criteria decision-making (MCDM) aid in prioritizing risk strategies. Case studies show that MCDM can reduce disruption time by up to 25% and improve supplier diversification in sectors like pharmaceuticals and agriculture. The review highlights the importance of integrated, context-sensitive approaches and calls for future research into region-specific models, longitudinal studies, and interdisciplinary methods for sustainable supply chain management